Understanding risk : the theory and practice of financial risk management - Murphy, David (Boca Raton : Chapman & Hall/CRC, 2008)
The book explains how to understand financial risk and how the severity and frequency of losses can be controlled. The book covers the basics of risk management and the behaviour of financial instruments. It also focuses on regulatory capital standards and models, addressing value-at-risk (VaR) models, portfolio credit risk, tranching, operational risk, and the Basel accords. The author also dealt with assets/liability management (ALM) and liquidity management, structured finance and a variety of new trading instruments, including inflation-linked products, sophisticated equity basket options, and convertible bonds.
Includes bibliographical references and index.
rpm 30/05/13
Loans
Keywords: Financial risk management; Investment analysis; Portfolio management